Cadmium and lead levels in three freshwater fish species from the Zambezi region, Namibia. Issue 4 (1st October 2020) - Madzingira, O; Lifumbela, LZ; Kandiwa, E; Kandjengo, L; Mushonga, B
Abstract : Muscle tissue from three-spotted tilapia ( Oreochromis andersonii ) ( n = 11), sharp tooth catfish ( Clarias gariepinus ) ( n = 14) and tigerfish ( Hydrocynus vittatus ) ( n = 12) were sampled from a market in the Zambezi region, Namibia in June 2018 and analysed for cadmium and lead. Cadmium was not detected in the three fish species. Mean lead levels in all three fish species (0.09–0.19 mg kg−1) were below the recommended safe level of 0.3 mg kg−1. Catfish had the highest mean lead concentrations, followed by tigerfish and tilapia in descending order. However, the differences in mean lead concentrations between the three fish species were not statistically significant (ANOVA, p = 0.18). These results show that the fish tested were safe for human consumption with respect to the metals tested. It is recommended that more metals and other contaminants, such as pesticides, be monitored robustly in water, sediment and fish, using the recommended protocols, in order to generate data that can be reliably used for human health risk assessments in the future.